Smart Drive Assist Systems for Modern Vehicles: A Review of Current Advances and Future Directions - Dipanshu Samudrasok; Anuradha Pandit; Yash Shivatare; Saurabh Sharma (International Journal of Advanced Control and System Engineering, 2024)
Smart drive assist systems serve as advanced automotive companions, boasting three pivotal capabilities: blind spot monitoring, collision prevention, and adaptive lighting. Blind spot monitoring acts as a vigilant sentinel, overseeing areas beyond the driver's direct view and issuing alerts for potential blind spot intrusions during lane changes. Collision prevention acts as a protective shield, scanning the road ahead to notify the driver of impending collisions, affording crucial reaction time to avert accidents. Adaptive lighting functions as an illuminating guide, intelligently adjusting its beam direction to ensure optimal visibility for the driver while minimizing glare for oncoming traffic, thereby enhancing safety and comfort during nighttime journeys. These smart drive assist features work seamlessly together to elevate the overall driving experience, promoting enhanced safety and convenience. Blind spot detection systems are designed to act as vigilant lookouts, issuing warnings for potential intrusions into the driver’s blind spots during lane changes. These systems continuously scan the areas behind and next to the car that are hidden from the driver's view by conventional mirrors using a combination of sensors, cameras, and radar technologies. The technology helps to prevent collisions that frequently happen during lane-changing maneuvers by informing the driver when a vehicle is identified in the blind spot by visual indications, such as lights on the side mirrors, or audible warnings.
Keywords: Arduino NANO; Smart drive assist system (SDAS); TF Luna LiDAR sensor; adjustable headlight; blind spot detection; collision alert; potentiometer; time-of-flight ToF light detection and ranging (LiDAR) sensor